EKSPLORASI JAMUR GANODERMA APPLANATUM DENGAN HIASAN RUFFLE PADA BUSANA PESTA SORE - ati Taryati; feny puspitasari (Universitas Pendidikan Indonesia, 2018)
Energy crisis and environmental destruction of human creation, reviving the thinking about the diversity of existing ecosystems in Indonesia. The diversity of ecosystems that can enhance the natural beauty of Indonesia, one of the decomposer organism is Ganoderma Applanatum Mushroom. Ganoderma applanatum in the ecosystem acts as a decomposer or decomposing dead organism that is capable of maintaining an organic nutrient supply which is essential for plant growth. Structurally Ganoderma Applanatum has a very unique form, from here came the thought to make a fashion work by exploring the shapes of ganoderma applanatum in the existing party dress. Visualization of Ganoderma Applanatum is represented of Ruffle that produces the details of the shape of the bend. This impression represents of Ganoderma Applanatum. Ruffle is applied to the evening party dress at the peplum top. The method used is Project Based Learning supported by literature study and documentation. The product results in addition to creating an evening party dress by exploring of Ganoderma Applanatum Mushroom as decorative trim, also expected to bring Indonesian fashion more contemporary.Keywords: ganoderma mushroom, ruffle, evening party dress